Synthesis of (2R, 8′S, 3′E)-δ-tocodienol, a tocoflexol family member designed to have a superior pharmacokinetic profile compared to δ-tocotrienol. Issue 27 (7th July 2016) - Liu, Xingui; Gujarathi, Satheesh; Zhang, Xuan; Shao, Lijian; Boerma, Marjan; Compadre, Cesar M.; Crooks, Peter A.; Hauer-Jensen, Martin; Zhou, Daohong; Zheng, Guangrong
Abstract: A group of side chain partially saturated tocotrienol analogues, namely tocoflexols, have been previously designed in an effort to improve the pharmacokinetic properties of tocotrienols. (2 R, 8′ S, 3′ E )-δ-Tocodienol (1 ) was predicted to be a high value tocoflexol for further pharmacological evaluation. We now report here an efficient eight-step synthetic route to compound1 utilizing naturally-occurring δ-tocotrienol as a starting material (24% total yield). The key step in the synthesis is oxidative olefin cleavage of δ-tocotrienol to afford the chroman core of1 with retention of chirality at the C-2 stereocenter. Graphical abstract: